The influence of barosok trading system on ethical business behavior in the husbandry sector in West Sumatera - NOVERI MAULANA (Journal of Advanced Research in Social Sciences and Humanities, 2017)
Aim: The purpose of this study is to provide a detailed description of the barosok maxim and its connections to Kant’s ethical theory as they pertain to the West Sumatera animal market.Methodology: Qualitative research methods were used in this exploratory study. In the deductive approach, interviews are used to collect data, which is then analyzed using content analysis.Findings: The model of categorical imperatives outlined in the Kantian Theory was found to be related to the central values of Barosok through research. The implementation of Kantian Theory on business ethics in the barosok tradition in West Sumatera is still being used today, even though the research also discovered an ethical conundrum among market participants.Implications/Novelty: Ethical investigations into Indonesia’s animal-trade industries can benefit from this study. In the future, researchers may examine the barosok method’s ethical value in light of Indonesian legislation.